PENGELOLAAN PERTAMBANGAN MINERAL DAN BATU BARA PERSPEKTIF SIYASAH DUSTURIYAH - AlMubarok; Agustina Nurhayati; Ahmad Burhanuddin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The main issue of this research is the controversy over Article 162 of Law No. 3 of 2020 on Mineral and Coal Mining, which potentially criminalizes anti-mining communities and contradicts social justice values. The research questions are: (1) what are the problems in mining management under Article 162, and (2) how does Siyasah Dusturiyah view mining management by business actors according to this article. This study uses a normative juridical method with conceptual and statutory approaches. The findings reveal: (1) Article 162 contains vague terms such as “obstructing” and “disturbing,” causing legal uncertainty and violating community rights; (2) from the Siyasah Dusturiyah perspective, it fails to uphold justice (al-‘adl), accountability (al-mas’uliyyah), and public welfare (maslahah ‘ammah); and (3) it contradicts maqashid al-syari‘ah by favoring corporate interests over social and environmental protection.